The Upper Proterozoic and Phanerozoic Geology of North-Western New South Wales (The Australasian Institute of Mining and Metallurgy, 1969)
The geology of an area in north-western New South Wales, bounded by the South Australian and Queensland borders, latitude 32° S. and longitude 14° E. is discussed.The area involved includes sixteen 1:250,000 standard military sheets and covers approximately 96,000 sq. miles.The geology of the Willyama Complex is not dealt with but a small area of metasediments previously included in this unit is separated and a possible correlation with Precambrian to the east is suggested. Torrowangee Group sediments are described and the problem of nomenclature using a glacial implication is raised.Nine areas of proven Lower Palaeozoic sediments are considered and their relationship to the boundaries of the Bancannia Trough outlined. It is possible that some exposures not yet substantiated by fossil evidence may prove to be Lower Palaeozoic rather than Precambrian in age.The sediments of the Lachlan Geosyncline in the area of the Cobar massif are described and new concepts on the age and distribution of some of the established stratigraphic units are introduced. The absence of rocks of Middle Silurian age probably indicates the time of a major orogeny in this area.Lithology, thickness, and distribution of the Upper Devonian sediments is considered and some of the more recently found fish plate localities are listed.Mesozoic sediments occur in isolated areas of Lower Jurassic age and in the Great Australian (Artesian) Basin. A four-fold subdivision of sediments of the basin has been possible in some areas but lack of sub-surface information at present, precludes the possibility of correlation with the type sections in Queensland.Units in the Cainozoic are subdivided and a five fold subdivision of the Quaternary, at present being used throughout western New South Wales, is described.